Energizing Porters by Proton-Motive Force - Nelson, Nathan (Journal of experimental biology, 1994)
It is generally accepted that the chemistry of water was the most crucial determinant in shaping life on earth. Among the more important chemical features of water is its dissociation into protons and hydroxyl ions. The presence of relatively high proton concentrations in the ambient solution resulted in the evolution of proton pumps during the dawn of life on earth. These proton pumps maintained neutral pH inside the cells and generated electrochemical gradients of protons (proton-motive force) across their membranes. The existence of proton-motive force enabled the evolution of porters driven by it that are most probably among the more primitive porters in the world. The directionality of the substrate transport by the porters could be to both sides of the membranes because they can serve as proton symporters or antiporters. One of the most important subjects of this meeting is the mechanism by which proton-motive and other ion-motive forces drive the transport processes through porters. Is there a common mechanism of action for all proton-driven porters? Is there some common partial reaction by which we can identify the way that porters are energized by proton-motive force? Is there a common coupling between proton movement and uptake or secretion of certain molecules? Even a partial answer to one of these questions would advance our knowledge… or confusion. As my mentor Efraim Racker used to say: ‘If you are not totally confused you do not understand the issue’.